2012
DOI: 10.1155/2012/532418
|View full text |Cite
|
Sign up to set email alerts
|

Biological Fingerprinting of Herbal Samples by Means of Liquid Chromatography

Abstract: Biological chromatographic fingerprinting is a relatively new concept in the quality control of herbal samples. Originally it has been developed with the application of HPLC, and recently herbal samples' biological profiles have been obtained by means of thin-layer chromatography (TLC). This paper summarizes the application of liquid chromatographic techniques for the purpose of biological fingerprint analysis (BFA) of complex herbal samples. In case of biological TLC fingerprint, which is a relatively novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Fingerprint construction is helpful to detect adulterations, to control the process of extraction, and to test the quality of a finished product. Herbal sample fingerprints are a set of characteristic chromatographic or spectroscopic signals that enable sample recognition through comparison (Ciesla 2012). While many chromatographic methods have been used for fingerprint construction Springfield et al (2005) suggested that fingerprinting using HPLC is the best method for extract characterization.…”
Section: Discussionmentioning
confidence: 99%
“…Fingerprint construction is helpful to detect adulterations, to control the process of extraction, and to test the quality of a finished product. Herbal sample fingerprints are a set of characteristic chromatographic or spectroscopic signals that enable sample recognition through comparison (Ciesla 2012). While many chromatographic methods have been used for fingerprint construction Springfield et al (2005) suggested that fingerprinting using HPLC is the best method for extract characterization.…”
Section: Discussionmentioning
confidence: 99%
“…It was originally developed with the use of high-performance liquid chromatography. Apart from qualitative and quantitative data, it gives also the possibility to fish out the active compounds from a myriad of compounds present in herbal samples 3 . Chemical fingerprinting has been demonstrated to be a powerful technique for the quality control of herbal medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Bioassay-coupled chromatography has also found application in biological finger printing of herbal samples. 8 Herbal finger printing involves a set of characteristic chromatographic and spectroscopic signals which lead to unambiguous sample identification upon comparison with reference(s). However, since traditional chromatographic analysis could only provide qualitative and quantitative information, compounds present in low concentration which may be responsible for the biological activity of the sample may not be detected.…”
Section: Introductionmentioning
confidence: 99%
“…However, since traditional chromatographic analysis could only provide qualitative and quantitative information, compounds present in low concentration which may be responsible for the biological activity of the sample may not be detected. 8 Thus, the need to add a system which involves bioassay coupled with chromatography and spectroscopy. In the search for active compounds from highly complex sample mixtures such as in the field of natural product research, target analysis only is ineffective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation